A2. A longitudinal study of endothelial function during normal pregnancy. (12th August 2016) - Iacobaeus, Charlotte; Andolf, Ellika; Bremme, Katarina; Jörneskog, Gun; Östlund, Eva; Thorsell, Malin; Khan, Thomas
Abstract: Aim : This study aimed to examine alterations in maternal endothelial function during normal pregnancy. Methods : We assessed endothelial function in the brachial artery (by post-ischemic hyperemia-induced flow-mediated vasodilation and glyceryl nitrate) and in the forearm skin microcirculation (by laser Doppler perfusion imaging and iontophoretic administration of acetylcholine (Ach) and sodium nitroprusside (SNP)) in 53 healthy primiparous women at 14, 24 and 34 weeks of gestation, and nine months post-partum (non-pregnant state). Results : Flow-mediated vasodilation in the brachial artery (FMD) increased during early pregnancy, whereas nonspecific vasodilatation by glyceryl trinitrate (GTN) decreased, indicating improved endothelial function. Consistent with this, endothelium-dependent skin microvascular reactivity to Ach also increased. Discussion : Normal pregnancy is associated with increased endothelial function assessed both in the brachial artery and in the forearm skin microcirculation.